PENGEMBANGAN EVALUASI PEMBELAJARAN MATEMATIKA MENGGUNAKAN QUIZWHIZZER PADA MATERI SUDUT - Siti Aulia Sopiyah; Nita Karmila; Nurlinda Safitri (STKIP Subang, 2025)
This research is a Research and Development (R&D) research with the ADDIEdevelopment model (analysis, design, development, implementation and evaluation),which aims to develop and determine the feasibility of Mathematics learningevaluation using QuizWhizzer on angle material. This study involved 28 fifth gradestudents of SDN Pagelaran 03 in the even semester of the 2024-2025 school year.The stages start from needs analysis, design planning, development of learningevaluation on the QuizWhizzer platform, to limited trials in class. The results of thestudy showed that the validation of media experts was 98%, language experts were100%, lecturer material experts were 100%, and teacher material experts were 96%,the average percentage of overall validation results was 98.5%, with the category"Very Feasible". Strengthened by the results of student responses of 94.7% andteacher responses of 97% including the category of